The anarchist farmer woman: a gender role and aesthetic study in the Mujeres Libres Spanish magazine (1936-1938) - Ojeda Muñoz, Noelia; García Ramos, María Dolores (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In the 1930 decade in Spain, during the Civil War, the anarchist organization Mujeres Libres (Free women) was concerned about the situation of the farmer woman. These women had means for reflection and dissemination of their ideals: the Mujeres Libres Spanish magazine (1936-1938). The magazine was aimed at activist and supporter women of the libertarian movement, and the objective was reflect on the situation of these women in all scopes. In this article we are going to analyse the ideal, aesthetic and roles given to the anarchist farmer woman in the texts and images of this publication.